Comparison of short-pulse subthreshold (532 nm) and infrared micropulse (810 nm) macular laser for diabetic macular edema - Abdulrahman Al-Barki (Nature Portfolio, 2021)
Abstract The purpose of the study was to assess both anatomic and functional outcomes between short-pulse continuous wavelength and infrared micropulse lasers in the treatment of DME. This was a prospective interventional study from tertiary care eye hospital—King Khaled Eye Specialist Hospital (Riyadh, Saudi Arabia). Patients with center-involving diabetic macular edema were treated with subthreshold laser therapy. Patients in the micropulse group were treated with the 810-nm diode micropulse scanning laser TxCell (IRIDEX Corporation, Mountain View, CA, USA) (subthreshold micropulse—STMP group). Laser was applied according to recommendations for MicroPulse (125 microns spot size, 300 ms pulse duration and power adjustment following barely visible testing burn) in a confluent mode (low intensity/high density) to the entire area of the macular edema. Patients in the short-pulse group were treated with grid pattern laser with 20 ms pulse PASCAL laser 532 nm (TopCon Medical Laser Systems, Tokyo, Japan) with EndPoint algorithm, which was either 30% or 50% of testing burn (EndPoint 30% and EndPoint 50% groups, respectively). Main outcome measures included best-corrected visual acuity (BCVA in logMAR) and foveal thickness at baseline and the last follow-up visit at 6 months. There were 44 eyes in the micropulse group, 54 eyes in the EndPoint 50% group and 18 eyes in the EndPoint 30% group. BCVA for the whole cohort (logMAR) was 0.451 (Snellen equivalent 20/56) at baseline, 0.495 (Snellen equivalent 20/62) (p = 0.053) at 3 months, and 0.494 (Snellen equivalent 20/62) at the last follow-up (p = 0.052). Foveal thickness for the whole cohort was 378.2 ± 51.7 microns at baseline, 347.2 ± 61.3 microns (p = 0.002) at 3 months, and 346.0 ± 24.6 microns at the final follow-up (p = 0.027). As such the short-pulse system yields more temporary reduction in edema. Comparison of BCVA between baseline and 6 months for EndPoint 30%, EndPoint 50% and STMP groups was p = 0.88, p = 0.76 and p = 0.003, respectively. Comparison of foveal thickness between baseline and 6 months for EndPoint 30%, EndPoint 50% and STMP groups was p = 0.38, p = 0.22 and p = 0.14, respectively. We conclude that the infrared micropulse system seems to improve functional outcomes. When applied according to previously published reports, short-pulse system may yield more temporary reduction in edema while infrared micropulse system may yield slightly better functional outcomes.